2011
DOI: 10.1111/j.1601-0825.2011.01800.x
|View full text |Cite
|
Sign up to set email alerts
|

Higher prevalence of periodontitis in patients with refractory arterial hypertension: a case–control study

Abstract: Severe and generalized chronic periodontitis seem to play a role as risk indicators for hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 29 publications
4
13
0
2
Order By: Relevance
“…In the present study, it was observed that patients with hypertension had, on average, a greater number of teeth with deepened (4 mm deep or deeper) or deep (6 mm deep or deeper) periodontal pockets and more gingival bleeding than normotensive (systolic blood pressure ≤140 mmHg, diastolic blood pressure ≤90 mmHg) subjects. These observations concur with what can be seen, for example, in the study by Vidal and his group (), who reported that hypertensive patients had a higher proportion of sites with dental plaque, gingival bleeding and number and proportion of sites with clinical attachment loss (6 mm or more) than did non‐hypertensive patients. They also are consistent with the findings of Yamori et al.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, it was observed that patients with hypertension had, on average, a greater number of teeth with deepened (4 mm deep or deeper) or deep (6 mm deep or deeper) periodontal pockets and more gingival bleeding than normotensive (systolic blood pressure ≤140 mmHg, diastolic blood pressure ≤90 mmHg) subjects. These observations concur with what can be seen, for example, in the study by Vidal and his group (), who reported that hypertensive patients had a higher proportion of sites with dental plaque, gingival bleeding and number and proportion of sites with clinical attachment loss (6 mm or more) than did non‐hypertensive patients. They also are consistent with the findings of Yamori et al.…”
Section: Discussionsupporting
confidence: 90%
“…Although periodontitis is a local process, it has been associated with a range of non-oral diseases including atherosclerotic vascular diseases (Weidlich et al 2008, Lockhart et al 2012). An association between clinically defined periodontitis (Tsakos et al 2010, Vidal et al 2011, Yamori et al 2011, severe periodontitis (Rivas-Tumanyan et al 2013) and periodontal bacterial burden, measured either by means of the number of periodontal pathogens (Desvarieux et al 2010) or colonization by single periodontal pathogens (Tsioufis et al 2011), and elevated blood pressure has been reported. On the other hand, no association between self-reported periodontitis and hypertension was found in the Health Professionals study with a 20 follow-up (Rivas-Tumanyan et al 2012).…”
mentioning
confidence: 99%
“…Chronically elevated levels of systemic inflammation could mediate association between periodontitis and hypertension because both conditions have been linked to inflammation 18 . Indeed, epidemiologic studies and some clinical studies suggest a potential linkage between periodontitis and hypertension 14 , 40 , 41 . However, many studies reporting the association between periodontitis and hypertension were cross‐sectional in design and either did not make any adjustments or only adjusted for a small number of potential confounders 14 , 40 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, epidemiologic studies and some clinical studies suggest a potential linkage between periodontitis and hypertension 14 , 40 , 41 . However, many studies reporting the association between periodontitis and hypertension were cross‐sectional in design and either did not make any adjustments or only adjusted for a small number of potential confounders 14 , 40 , 42 . Also, some of these investigations were not designed with the primary aim of testing the link between periodontitis and hypertension 15 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, outros estudos demonstram que pacientes hipertensos apresentam maior proporção de lugares com placa bacteriana, sangramento gengival e sítios com perda de inserção clinica do que os pacientes não hipertensos (VIDAL et al, 2011;RIVAS-TUMANYAN et al, 2013).…”
Section: Condição Periodontal Nível De Inserção Clínicaunclassified